Attitudes towards sexuality in Peruvian adolescents - Nataly Choco Zegarra; Alexandra Mercedes Salluca Yana; Jose Calizaya-Lopez (Environment and Social Psychology, 2025)
Adolescence is an important stage for the construction of identity, where sexuality acquires a central role, in the Peruvian context, cultural and family patterns tend to strengthen conservative visions, conditioning adolescents’ attitudes towards sexuality. The aim of this study was to analyze attitudes towards sexuality in Peruvian adolescents, considering sociodemographic characteristics and the cultural context in which they develop. Method. The study was observational and cross-sectional, with a quantitative approach; 1865 adolescents intentionally selected in five educational institutions participated; The scale of attitudes towards sexuality was applied, the data were analyzed using non-parametric tests, with calculation of effect sizes. Results. It was found that more than 90% of the adolescents evaluated presented conservative attitudes towards sexuality, evidencing a strong influence of family, religious and sociocultural factors in the configuration of these attitudes. It is concluded that these predominant conservative attitudes reflect the validity of traditional values in the socialization of adolescents, likewise, there is a need to strengthen comprehensive sex education programs that promote objective information, responsibility and autonomy in the experience of sexuality.